ChemInform Abstract: Rhodium‐Catalyzed Tandem Cyclization/Si—C Activation Reaction for the Synthesis of Siloles. Issue 46 (18th November 2014) - Zhang, Qing‐Wei; An, Kun; He, Wei
Abstract A highly efficient and practical new synthetic strategy for the synthesis of structurally diverse siloles, including the first examples of benzofuran siloles [(XI) and (XII)], is developed.